2018
DOI: 10.13189/ujer.2018.060114
|View full text |Cite
|
Sign up to set email alerts
|

Social Support and Coping Styles in Predicting Suicide Probability among Turkish Adolescents

Abstract: This study aims to investigate whether the perceived social support and coping styles are predictors of suicide probability by gender. The study was conducted with 445 high schools students, 227 girls, and 218 boys. The participants were aged between 14 and 18, and their average age was 15.90. Data were collected through the 'Multidimensional Scale of Perceived Social Support', the 'Ways of Coping Questionnaire', and the 'Suicide Probability Scale'. Data were analyzed using MANOVA, Pearson correlation test and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
1
8
0
4
Order By: Relevance
“…For instance, a client's behavioral pattern for solving problems and adversities could be a basic index for clinicians in initial screening. Moreover, social support and social contact could be protective factors against suicidal ideation (Cenkseven‐Önder, ), which could also be taken into consideration in the screening process. Even more, in terms of implications for treatment, teaching effective coping strategies, especially reappraisal coping and approach coping, could be a treatment alternative that helps high‐risk individuals reduce their degree of suicidal ideation (Tang & Qin, ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a client's behavioral pattern for solving problems and adversities could be a basic index for clinicians in initial screening. Moreover, social support and social contact could be protective factors against suicidal ideation (Cenkseven‐Önder, ), which could also be taken into consideration in the screening process. Even more, in terms of implications for treatment, teaching effective coping strategies, especially reappraisal coping and approach coping, could be a treatment alternative that helps high‐risk individuals reduce their degree of suicidal ideation (Tang & Qin, ).…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of suicide and suicidal thoughts is an old issue in the medical world, and this issue is still one of the things that are highlighted and hidden because of the bad stigma attached to doctors or medical students with mental emotional problems. Research on this subject has always consistently shown that medical students have a high prevalence of depression, burnout, and emotional disorders, as well as a higher risk of having suicidal thoughts [9][10][11]. The risk of suicidal thoughts is associated with several factors, including individual factors, family and academic situations.…”
Section: Suicide and Risk Factors In Medical Studentsmentioning
confidence: 99%
“…Penelitian lain yang dilakukan Liu (2011) pada pemuda Asia juga menunjukkan adanya hubungan signifikan yang negatif antara dukungan sosial keluarga dengan ide bunuh diri. Keluarga adalah sumber dukungan primer yang dihubungkan dengan rendahnya ide bunuh diri (Cenkseven-Őnder, 2018). Walaupun teman dan significant others adalah sumber dukungan penting bagi mahasiswa, dukungan keluarga adalah sumber yang lebih penting terutama dalam situasi traumatik (Lai & Ma, 2016).…”
Section: Hubungan Dukungan Sosial Keluarga Dengan Ide Bunuh Diriunclassified